Role of mobile technology in anti - counterfeit initiatives in Kenya: case of electronic products - Munga, Harun Karuri (iLabAfrica, 2014)
Counterfeiting has had devastating effects in the global market and more especially in recent times. This can be attributed to the fact that counterfeiting has become more sophisticated and as the world transforms into a “global village” its effects are more adverse and far reaching than ever before. Closer home, Kenya is no exception and is among one of country most affected by the continued trade in counterfeits in the region even as industry-wide efforts are made to contain it. Kenya has instituted diverse strategies in the fight against counterfeiting with a view to eradicating it and in recognition of its far reaching effects. However, findings from this research intimate that a good number of the anti counterfeiting measures have not been successful due to several factors but largely due to underfunding to those tasked with fighting the vice especially the Anti Counterfeiting Agency [ACA]. Recent reports in the telecommunication industry in Kenya, suggest that more than half of the population has a mobile device and the number of Kenyans accessing the internet through their mobile devices continues to soar. Additionally, smart phones have continually become cheaper putting them within reach of a majority of Kenyans. The research seeks to opportune on these developments, to provide consumers with a simple, efficient and effective technique to authenticate if a product is genuine or otherwise before making a purchase. Through the use of mobile technology, this research proposes a mobile web authentication solution that can be used to establish the authenticity of products. The solution is available to web enabled smart phones with camera capabilities and a custom Quick Response (QR) code application with consumers receiving a message verifying or rejecting the authenticity of a product.
A dissertation submitted in partial fulfillment of the requirements for the Degree of Master of Science in Mobile Telecommunications and Innovation